The Perception of “Beautiful” Indonesian Women in The Eka Kurniawan’s Novel “Beauty is a Wound” - Alfi Thoyyibah; Dinanil Funun El Milal (International Journal of English Learning and Applied Linguistics (IJELAL), 2023)
Literature is a manifestation of the existence of life in society. Literature as a means of cultural and social representation that describes gender relations. One of the literary criticisms, there is a view called feminism, namely the women's movement caused by the awareness that women have the same rights as men. This article aims to discuss or analyze perceptions or views about the expression 'beautiful' for Indonesian women in the novel "Beauty is a wound" by Eka Kurniawan. The writer concludes that this research is included in the field of literary criticism, therefore in this study the writer uses a qualitative method with descriptive analysis, namely this research is case study research. This study is based on the theory of feminism analysis, in which from time to time the concept of women's beauty changes, from being purely sexual to political. The results of the analysis show that the term "beautiful" in the main character Dewi Ayu is reflected in her attitude, such as her appearance, intelligence, generosity, and courage in the figure of Dewi Ayu in the novel "Beauty is a Wound".